Use of Mycorrhiza to Reduce Mineral Fertilizers in Soilless Melon (Cucumis melo L.) Cultivation - Dere, Sultan; Daşgan, Hayriye Yıldız; Çoban, Ayşe; Akhoundnejad, Yelderem; Özsoy, Süleyman (UNIV AGR SCI & VETERINARY MED CLUJ-NAPOCA, 2019)
Intensive use of mineral fertilizers in soilless growing systems can have adverse effects on the environment and human health and could be economically expensive. Aim of this study was whether it can be reduced mineral nutrients in soilless grown melon by using mycorrhizae inoculation. The experiment has been carried out in the early spring growing period in a greenhouse in the Mediterranean climate. The eight treatments have been applied: (1) 100% Full nutrition (control), (2) 100% Full nutrition+mycorrhiza, (3) 80% nutrition, (4) 80% nutrition+mycorrhiza (5) 60% nutrition (6) 60% nutrition+mycorrhiza (7) 40% nutrition, (8) 40% nutrition+mycorrhiza. Effects of mycorrhiza on melon plant growth, yield, fruit quality, and leaf nutrient concentrations were investigated. Arbuscular mycorrhizal fungi colonization is accompanied by plant growth increases in reduced nutrient levels. The mycorrhiza inoculation had a significant enhancing effect on total yield in soilless grown melon plants. The highest increasing effect on melon yield was observed in the “80% nutrient+mycorrhiza”, and AM- inoculated plants produced 49.5% higher melon yield (12.4 kg m-2) than that of control plants without mycorrhizae (8.3 k gm-2). AM-inoculation was also able to establish an improvement in Brix and EC of melon fruit. In the nutrient contents of leaves, there were slight increases in AM-inoculated plants, except P. The P content was significantly increased in AM-inoculated 80% nutrient plants as comparison to that of its control.
Keywords: Brix in melon; Hydroponics; Plant growth; Yield